Linux Administration Best Practices : Practical Solutions to Approaching the Design and Management of Linux Systems - Miller, Scott Alan (Packt Publishing, Limited, 2022)
Gain an understanding of system administration that will remain applicable throughout your career and understand why tasks are done rather than how to do them Key Features Deploy, secure, and maintain your Linux system in the best possible way Discover best practices to implement core system administration tasks in Linux Explore real-world decisions, tasks, and solutions involved in Linux system administration Book Description Linux is a well-known, open source Unix-family operating system that is the most widely used OS today. Linux looks set for a bright future for decades to come, but system administration is rarely studied beyond learning rote tasks or following vendor guidelines. To truly excel at Linux administration, you need to understand how these systems work and learn to make strategic decisions regarding them. Linux Administration Best Practices helps you to explore best practices for efficiently administering Linux systems and servers. This Linux book covers a wide variety of topics from installation and deployment through to managing permissions, with each topic beginning with an overview of the key concepts followed by practical examples of best practices and solutions. You'll find out how to approach system administration, Linux, and IT in general, put technology into proper business context, and rethink your approach to technical decision making. Finally, the book concludes by helping you to understand best practices for troubleshooting Linux systems and servers that'll enable you to grow in your career as well as in any aspect of IT and business. By the end of this Linux administration book, you'll have gained the knowledge needed to take your Linux administration skills to the next level. What you will learn Find out how to conceptualize the system administrator role Understand the key values of risk assessment in administration Apply technical skills to the IT business context Discover best practices for working with Linux specific system technologies Understand the reasoning behind system administration best practices Develop out-of-the-box thinking for everything from reboots to backups to triage Prioritize, triage, and plan for disasters and recoveries Discover the psychology behind administration duties Who this book is for This book is for anyone looking to fully understand the role and practices of being a professional system administrator, as well as for system engineers, system administrators, and anyone in IT or management who wants to understand the administration career path. The book assumes a basic understanding of Linux, including the command line, and an understanding of how to research individual tasks. Basic working knowledge of Linux systems and servers is expected.